Implementation Of Active Knowledge Sharing Strategy To Improve Student Learning Activities In Islamic Education - Fitria Rahmadani; Nurul Latifatul Inayati (Institut Agama Islam An-Nawawi Purworejo, 2025)
The purpose of this study was to examine whether implementing an active knowledge sharing strategy can improve students' learning activities in Islamic religious lessons at SMA Batik 1 Surakarta. This research method uses descriptive techniques. Data collection methods include documentation, interviews, and observations. Data analysis was carried out using a non-statistical approach in which data were analyzed in the form of collected interviews, observation notes, and document results. The results of the study concluded that the active knowledge sharing strategy can improve student activity. This strategy will always use opinions and answers from others. However, teachers do not routinely use the use of active knowledge exchange because they rely on the material presented. So, a more optimal application is needed to improve learning activities for students in Islamic Religious Education subjects. The active knowledge sharing strategy in Islamic Religious Education learning can also improve learning effectiveness by optimizing student participation, building mutual respect and empathy, and promoting a deeper understanding of the learning material.